HABITUALIZATION OF FURUDLUL AINIYAH (FA) FOR EARLY CHILDHOOD:PKM Fostering FA Through the Demonstration Methodat Mardasah Diniyah Raidlatul Muta'allimin Probolinggo - Ainul Yakin; Ahmad Zainur Razikin; Ahmad Farid Syauqi; Muhammad Axzal Revansyah; Saddan Husain (SINAR: Sinergi Pengabdian dan Inovasi untuk Masyarakat, 2024)
This Community Service (PKM) activity aims to foster the habitualization of Furudhul Ainiyah (FA) in early childhood through the application of the demonstration method at Madrasah Diniyah Raudlatul Muta'allimin, Probolinggo. Furudhul Ainiyah refers to the obligation of individuals to carry out mandatory worship such as prayer, fasting, reading the Qur'an and ablution, which requires habituation from an early age so that it becomes an integral part of a child's life. The demonstration method was chosen to provide practical understanding and actively involve children in the learning process. This activity began with the identification of needs, training for teachers, and the implementation of demonstration methods in fostering Furudhul Ainiyah. The results show that this method is effective in improving children's understanding and skills in carrying out compulsory worship independently. However, several obstacles were found, such as a lack of consistency in implementation at home and limited supporting facilities in madrasas. The proposed solutions include collaboration with parents in habituating worship at home and the provision of interactive learning media. The conclusion of this activity is that the demonstration method has a positive impact on forming worship habits in early childhood. This PKM is expected to be a model for other educational institutions that are committed to children's spiritual development.